Non-linear Conductance, Rectification, and Mechanosensitive Channel Formation of Lipid Membranes - Zecchi, Karis Amata; Heimburg, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Despite mounting evidence that lipid bilayers display conductive properties, when interpreting the electrical response of biological membranes they are commonly considered as inert insulators. However, lipid bilayers under voltage-clamp conditions do not only display current traces with discrete current-steps indistinguishable to those attributed to the presence of protein channels. In current-voltage plots they may also display outward rectification, i.e., voltage-gating. Surprisingly, this has even been observed in chemically symmetric lipid bilayers. Here, we investigate this phenomenon using a theoretical framework that models the electrostrictive effect of voltage on lipid membranes in the presence of a spontaneous polarization, which can be recognized by a voltage offset in electrical measurements. It can arise from an asymmetry of the membrane, for example from a nonzero spontaneous curvature of the membrane. This curvature can be caused by voltage via the flexoelectric effect, or by hydrostatic pressure differences across the membrane. Here, we describe current-voltage (I-V) relations for lipid membranes formed at the tip of patch pipettes situated close to an aqueous surface. We measured at different depths relative to air/water surface, resulting in different pressure gradients across the membrane. Both linear and nonlinear I-V profiles were observed. Nonlinear conduction consistently takes the form of outward rectified currents. We explain the conductance properties by two mechanisms: One leak current with constant conductance without pores, and a second process due to voltage-gated pore opening that correlates with the appearance of channel-like conduction steps. In some instances, these nonlinear I-V relations display a voltage regime in which dI/dV is negative. This has also been previously observed in the presence of sodium channels. Experiments at different depths reveal channel formation that depends on pressure gradients. Therefore, we find that the channels in the lipid membrane are both voltage-gated and mechanosensitive.